Electrical Properties of ZnO Thin Film Transistors - Paragjyoti Gogoi (Electrical Properties of ZnO Thin Film Transistors, 2024)
As a pivotal component in modern electronics devices, TFTs play a crucial role as a switching element in display and flexible electronics. This comprehensive work meticulously explores the electrical properties of ZnO TFTs, with different gate dielectrics offering a detailed investigation of the underlying materials, diverse fabrication techniques, and strategies for optimizing performance. The first section of the book provides a general introduction of the TFT, its applications and physical processes involved in TFT. A brief review of the works on TFTs is also introduced in this section. In the next section an insightful overview of the materials used and methodology adopted in fabrication of ZnO TFTs is presented. The core of the book focuses elaborately on the investigation of the electrical properties of ZnO TFTs with different gate dielectric materials such as Nd2O3, La2O3 and Al2O3 using different fabrication techniques viz. thermal evaporation, chemical bath deposition and sol-gel technique. Key aspects such as field effect mobility, threshold voltage, sub-threshold swing, gain bandwidth product etc. are explored in depth. Furthermore the effect of annealing temperature in ambient and oxygen atmosphere on the TFT characteristics are also investigated and presented.